Genome-wide chromatin contacts of super-enhancer-associated lncRNA identify LINC01013 as a regulator of fibrosis in the aortic valve - Chignon, Arnaud; Argaud, Déborah; Boulanger, Marie-Chloé; Mkannez, Ghada; Bon-Baret, Valentin; Li, Zhonglin; Thériault, Sébastien; Bossé, Yohan; Mathieu, Patrick (PLoS genetics, 2022)
Calcific aortic valve disease (CAVD) is characterized by a fibrocalcific process. The regulatory mechanisms that drive the fibrotic response in the aortic valve (AV) are poorly understood. Long noncoding RNAs derived from super-enhancers (lncRNA-SE) control gene expression and cell fate. Herein, multidimensional profiling including chromatin immunoprecipitation and sequencing, transposase-accessible chromatin sequencing, genome-wide 3D chromatin contacts of enhancer-promoter identified LINC01013 as an overexpressed lncRNA-SE during CAVD. LINC01013 is within a loop anchor, which has contact with the promoter of CCN2 (CTGF) located at ~180 kb upstream. Investigation showed that LINC01013 acts as a decoy factor for the negative transcription elongation factor E (NELF-E), whereby it controls the expression of CCN2 . LINC01013-CCN2 is part of a transforming growth factor beta 1 (TGFB1) network and exerts a control over fibrogenesis. These findings illustrate a novel mechanism whereby a dysregulated lncRNA-SE controls, through a looping process, the expression of CCN2 and fibrogenesis of the AV.